2001
DOI: 10.1051/rnd:2001129
|View full text |Cite
|
Sign up to set email alerts
|

Birth of piglets after OPS vitrification and transfer of compacted morula stage embryos with intact zona pellucida

Abstract: -In swine, five to six days post-insemination, morulae and blastocysts are collected together after uterine flushing. The purpose of this study was to vitrify zona pellucida-intact morulae with Open Pulled Straw (OPS) technology and obtain piglets after transfer. Morulae (200) were vitrified after a two-step equilibration in ethylene glycol, dimethyl sulfoxide and sucrose in Hepesbuffered TCM199 + 20% NBCS medium (TCM). 2-6 morulae were loaded into OPS and plunged into liquid nitrogen. At embryo warming, a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 14 publications
1
38
0
1
Order By: Relevance
“…Vajta [3] found that reducing this amount leads to faster cooling and a warming rate that allows embryos to rapidly pass through particular critical temperature zones, so that a higher survival rate was obtained compared to conventional vitrification. In fact, piglets have been successfully produced after transferring ultrarapidly vitrified embryos to recipient pigs [5][6][7][8]. The cooling and warming rate for the MVC-method used here is considered higher than that for conventional vitrification, because (i) the volume of vitrification medium surrounding embryos is smaller due to the excess solution being removed by pipetting after embryos were placed on the Cryotop blade and (ii) the embryos placed on the MVC plate can be directly exposed to LN and the warming medium in contrast to embryos being covered by a tip of a container such as GLT or ST filled with vitrification solution [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vajta [3] found that reducing this amount leads to faster cooling and a warming rate that allows embryos to rapidly pass through particular critical temperature zones, so that a higher survival rate was obtained compared to conventional vitrification. In fact, piglets have been successfully produced after transferring ultrarapidly vitrified embryos to recipient pigs [5][6][7][8]. The cooling and warming rate for the MVC-method used here is considered higher than that for conventional vitrification, because (i) the volume of vitrification medium surrounding embryos is smaller due to the excess solution being removed by pipetting after embryos were placed on the Cryotop blade and (ii) the embryos placed on the MVC plate can be directly exposed to LN and the warming medium in contrast to embryos being covered by a tip of a container such as GLT or ST filled with vitrification solution [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…T h i s t e c h n i q u e i s a s t a n d a r d cryopreservation procedure for porcine embryos mainly at the blastocyst stage [4][5][6][7][8]. In fact, several studies have reported live offspring production after transfer of vitrified porcine embryos [5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the in vitro development of vitrified embryos after rewarming was nearly 100%. Therefore, it is likely that similar numbers of piglets could be obtained by transferring fewer embryos than in this study; in other words, a higher production efficiency of piglets could be achieved.Production of pigs from vitrified in vivo-derived embryos has been achieved using blastocysts [40][41][42][43][44]. Pig blastocysts at later stages are known to be more cryotolerant than early cleavage stage embryos [45][46][47][48].…”
mentioning
confidence: 99%
“…Transfer of 147 vitrified expanded blastocysts into 10 recipients, resulted in birth of 29 live piglets, with pregnancy rate of 50% (Figure 2; Gajda et al, 2004). Recent application of the OPS method to pig blastocysts has allowed excellent in vitro survival (Berthelot et al, 2000(Berthelot et al, , 2001Gajda and Smorąg, 2001), but pregnancy rates after transfer are quite variable, ranging from zero to 60% (Gajda et al, 2006). …”
Section: Speciesmentioning
confidence: 99%